Atypical Antipsychotic Administration in Schizophrenic Patients Leads to Elevated Lipoprotein‐Associated Phospholipase A2 Levels and Increased Cardiovascular Risk: A Retrospective Cohort Study. Issue 6 (31st July 2018) - Shen, Hong; Wu, Danyang; Wang, Shanshan; Zhao, Mengjie; Sun, Wenbo; Zhu, Xiaozhou; Zhang, Ning; Yao, Hui; Cui, Qing; Xiao, Hong
Abstract: The prevalence of cardiovascular disease (CVD) is higher in patients with schizophrenia than in the general population. We aimed to investigate whether atypical antipsychotics (AAP) increase the levels of lipoprotein‐associated phospholipase A2 (Lp‐PLA2), thereby increasing the risk of CVD. The data were from inpatients aged 18–60 years with a diagnosis of schizophrenia according to ICD‐10 at the Affiliated Brain Hospital of Nanjing Medical University who underwent physical examination between 1 October 2014 and 30 September 2016. A retrospective cohort study was used to analyse the correlation between AAP, Lp‐PLA2 levels and the CVD risk (it was determined that Lp‐PLA2 values >200 ng/mL were defined as high CVD risk) in patients treated with monotherapy, olanzapine, clozapine or quetiapine. Data were collected for 452 patients with eligible schizophrenia: 163 treated with clozapine, 186 treated with olanzapine, 47 treated with quetiapine and 56 receiving no medication. Compared with the no‐medication patients, AAP administration in patients with olanzapine, clozapine or quetiapine had higher serum Lp‐PLA2 levels when age, sex, BMI and fasting glucose level were matched. AAP were significantly associated with serum Lp‐PLA2 level by Spearman's correlation coefficients. The results of logistic regression analysis showed that AAP administration was an independent factor of CVD risk when adjusted by potential confounding factors. This study is the first to confirm that AAP administration, especially clozapine and olanzapine, could increase Lp‐PLA2 levels and CVD risk, independent of drug‐induced weight gain in schizophrenia. The extent and the factors of increasing Lp‐PLA2 level and CVD risk in olanzapine, clozapine and quetiapine are discrepant. The possible effects of AAP on Lp‐PLA2 in schizophrenia patients are involved in pro‐inflammatory cytokines and hormones.